Food supply and demand outlook for South Asian countries policy implications for Indian Agriculture - Kumar, Praduman (Asian Journal of Agriculture and Development, 2010)
In South Asian Countries, the high population pressure on land and other natural resources to produce food and meet several development needs. South Asia accounts for 22 percent of the world's population on 3 percent of the global land area. Despite these constraints, South Asian countries have made remarkable progress in food production. These changes were triggered by the Green Revolution involving the development and diffusion of high yielding varieties (HYVs), especially of rice and wheat. from the mid-1960s onwards. This has been accompanied by increased levels of use of inputs, particularly irrigation, fertilizer and tractors, and policy support. Government investment in infrastructure, research and extension, price and other policies, along with strategies for crop, livestock and fisheries production, has significantly helped to increase food production and availability. The emerging production scenario, higher economic growth, population expulsion, and shifts in dietary pattern will change the supply and demand prospects for food in the 21st century. Producing additional food with limited and degraded natural resources and providing economic access to food at the household level to ensure food security for all will be the major challenge for South Asian nations. This paper aims to: 1) examine current situation and trends in food production, 2) project supply of food, 3) examine the food consumption pattern of households, 4) project the food demand, 5) estimate fix yield and production targets to maintain self-reliance among South Asian countries, and 6) suggest strategies to enhance food production. Earlier attempts were made by Rosegrant et. al. (1995), Paroda and Kumar (2000), Kumar and Mittal (2003), Kumar et al. (2007), and the Planning Commission (2007). This paper seeks to review the food supply and demand outlook using data of different food expenditure surveys and FAOSTAT food balance. Findings show that India is the major producer of food in South Asia and accounts for about 80 percent of the food requirement. Therefore, India has to play a major role not only to maintain self-sufficiency in food production but also to meet the additional requirement of its neighboring countries. The right research priorities and production strategies in India would promote future growth in agriculture and ensure sustainable food and nutrition security. Given the recent trends in consumption patterns, the demand for high-value food commodities in South Asia is likely to increase much faster than that of food grains. The additional demand for food grains as well as non-food grains has to come from productivity improvements, as the possibilities of area and livestock population expansion are extremely restricted. To meet the future demand for food and to maintain self-sufficiency, the South Asia region must attain a per hectar average yield of 2.4 tons for rice, 3.4 tons for coarse cereals, and 1.02 tons for pulses by year 2025. Productivity needs to be doubled for horticultural crops, livestock, and fisheries. The productivity growth targets are about 1 percent for cereals, 2 percent for pulses, 2.5 percent for edible oils, 3.5 percent for vegetables, fruits and milk, and 4 percent for meat, eggs, and fish. The required improvement in productivity needs serious efforts by the National Agricultural Research System, policymakers, and farmers in these countries. Looking at the supply and demand scenario, the food demand challenges are formidable considering the fast declining productivity growth, the shifting of cultivated land from cereals to non-cereals, and the rapidly shrinking resource base. Under the baseline scenario, cereal requirements will be met with marginal surplus of deficits but pulses will be in short supply. The slackness in investment on agricultural research and technology development as seen during early 1990s is a matter of concern in the context of continued increase in population, diminishing land and fresh water resources, expanding biotic and biotic stresses, increasing soil sanity and water logging problems, and decelerating productivity growth. The following are strategies recommended to enhance food production: 1) sustain green areas as green while, especially in the management of rice-wheat production systems, enhancing yield of major commodities, and arresting deceleration in toatl factor productivity, and implement integrated nutrient management; 2) turn gray areas to green by promoting available dry land technologies, increasing the stock of this knowledge, and removing pro-irrigation biases in pblic investment, expenditure, and credit flows; and 3) engage in agricultural diversification and calue-adding activities.